Analisi Hukum terhadap Jasa Makaler pada Usaha Jual Beli Sepeda Motor (Studi Kasus di Kecamatan Mutiara) - Nurliza; T. Sabirin (Jurnal Tahqiqa : Jurnal Ilmiah Pemikiran Hukum Islam, 2021)
This study aims to determine the practice of buying and selling vehicles using brokerage services as well as the view of Islamic law and positive law on brokerage services in buying and selling vehicles in Mutiara District. The research method used in the compilers of this thesis is a qualitative method, in obtaining data in the field the author uses several methods, namely using the library research method (library research), as well as the field research method (field research), namely by using interview, documentation, and observation techniques.. The results of the study indicate the calculation of brokerage services in marketing and its responsibility is to obtain a profit equal to each vehicle that is sold with a special calculation for the broker with Rp. 300.000, - from each vehicle sale, and the broker is responsible for promoting the goods if you want to make a profit. The calculation of brokerage services in marketing and its responsibility is to obtain a profit equal to each vehicle that is sold with a special calculation for the broker with Rp. 300.000, - from each vehicle sale, and the broker is responsible for promoting the goods if you want to make a profit. Brokerage services in buying and selling vehicles in Mutiara sub-district are in accordance with Islamic law and positive law as long as the broker and the owner of the goods or vehicle practice according to the agreement, for example, the vehicle owner gives the right to broker after obtaining the seller and according to the agreed agreement. So far, brokers in Mutiara District comply with positive laws because they carry out their jobs according to mandates.